Czech Republic : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Czech Republic. (IMF Staff Country Reports; Country Report ;, 2008)
The Czech Republic's strong fundamentals helped to sustain economic growth with low unemployment and underpin strides toward convergence with EU-15. Executive Directors welcomed the euro accession strategy and the sustained implementation of the Maastricht criteria, which would provide a solid foundation for euro adoption. They commended the sound financial system and prudent monetary policies and supported policy tightening to counter rising inflation pressures. Directors highlighted the need to sustain fiscal consolidation, promote labor participation, and lower structural unemployment in alleviating fiscal adjustment.